THE EFFECT OF COMMERCIAL FEEDING AND CONVENTIONAL FEEDS ON ISA BROWN CHICKENS ON THE QUALITY OF EGGS STORED FOR 28 DAYS - P. A. A., Yoga; Mahardika, I G.; Astawa, P. A. (Jurnal Peternakan Tropika; Vol 11 No 2 (2023): Vol. 11 No. 2 Tahun 2023; May - August, 2023)
This research aimed to determine the quality of chicken eggs given commercial and conventional rations on laying hens strain Isa Brown. This research was conducted in Candikusuma Village, Melaya District, Jembrana Regency, Bali which lasted for three months. The design used was a completely randomized design (CRD) with four treatments and four replications, so there were 16 experimental units. Each experimental unit used 10 laying hens. The four treatments were chickens fed a commercial feed (P0), chickens being given a conventional ration 1 (P1), chickens being given a conventional ration 2 (P2), chickens being given a conventional ration 3 (P3). The variables observed included egg weight, egg specific gravity, Haugh unit, egg yolk index and egg yolk color. The results showed that the conventional ration 1(P1) got the best results compared to other treatments on the variable egg weight (62.89g), egg specific gravity (1.21), haugh unit (60.03), egg yolk index (0,29) and egg yolk color (9). Based on the results of the study between the provision of commercial and conventional rations, it can be concluded that the conventional P1 ration produced higher egg weight, specific gravity, Haugh unit and egg yolk color compared to the provision of commercial, conventional rations P2 and P3, while the egg yolk index there was no difference. Keywords : Hens Isa Brown, egg quality,feed commercial, feed conventional